2016
DOI: 10.2337/db15-1606
|View full text |Cite
|
Sign up to set email alerts
|

B-Lymphocytes Expressing an Ig Specificity Recognizing the Pancreatic β-Cell Autoantigen Peripherin Are Potent Contributors to Type 1 Diabetes Development in NOD Mice

Abstract: Although the autoimmune destruction of pancreatic β-cells underlying type 1 diabetes (T1D) development is ultimately mediated by T cells in NOD mice and also likely in humans, B cells play an additional key pathogenic role. It appears that the expression of plasma membrane–bound Ig molecules that efficiently capture β-cell antigens allows autoreactive B cells that bypass normal tolerance induction processes to be the subset of antigen-presenting cells most efficiently activating diabetogenic T cells. NOD mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 41 publications
1
34
0
Order By: Relevance
“…Interestingly, FO, but not MZ B-lymphocytes preferentially expanded in mice that received transient combo therapy compared to controls (Figure 6B). Our past studies indicate B-lymphocytes entering the pancreatic islets of NOD mice have an FO-like phenotype (47). These rebounding, potentially diabetogenic, FO B-lymphocytes may explain the difference in T1D protection in NOD mice that underwent sustained versus transient combo treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, FO, but not MZ B-lymphocytes preferentially expanded in mice that received transient combo therapy compared to controls (Figure 6B). Our past studies indicate B-lymphocytes entering the pancreatic islets of NOD mice have an FO-like phenotype (47). These rebounding, potentially diabetogenic, FO B-lymphocytes may explain the difference in T1D protection in NOD mice that underwent sustained versus transient combo treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Of note, highly activated GC B cells do have increased ability to present antigens beyond those recognized by their BCRs, can cross present antigen to CD8 + T cells, and also produce inflammatory cytokines ( 14 , 15 ). It is also possible, as stated by Leeth et al ( 10 ), that the PerIg BCR cross-reacts with β-cell antigens or that β-cell antigens form complexes with peripherin that are internalized by the anti-peripherin BCR. These scenarios would promote epitope-spreading and widespread β-cell destruction by T cells that recognize autoantigens beyond peripherin.…”
mentioning
confidence: 96%
“…While there are multiple T1D-related autoantibodies in humans, to date, insulin has been the only reliable B cell–related autoantigen in NOD mice. In this issue of Diabetes , Leeth et al ( 10 ) report on a new transgenic model in which B cells recognize peripherin, a neuronal antigen, and are able to support diabetes development.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work has revealed that diabetes is associated with loss of anergy in insulin-binding B cells (13), and skewing B-cell specificity toward islet antigens can promote diabetes in mouse models (14,15). Although it is not believed that B cells or autoantibodies directly trigger b-cell destruction, recent evidence suggests that a high relative frequency of B cells within inflamed islets is associated with more aggressive and earlier onset T1D (16).…”
mentioning
confidence: 99%